Penggunaan Sistem Hidrolik Untuk Meningkatkan Efisiensi Energi dan Performa Operasional - Syahputra, Edy; Prabudi, Wisnu; Maqdis, Baitul; Syuhada, Ferry (universitas teuku umar, 2024)
This study examines the use of hydraulic systems in industrial equipment to improve energy efficiency and operational performance. Through a systematic literature review approach, this research analyzes various aspects of hydraulic system implementation in the context of modern industry. The results show that hydraulic systems offer significant advantages in terms of energy efficiency, with potential fuel savings of up to 40% and energy recovery efficiency reaching 53%. Various optimization strategies, including displacement control and implementation of Cyber-Physical Systems (CPS), prove effective in enhancing system performance. However, challenges such as high initial costs and the need for skilled labor still need to be addressed. Sustainability aspects are also a focus, with the use of bio-based hydraulic fluids that can reduce the carbon footprint by up to 30%. This study concludes that a deep understanding of the trade-offs between the benefits and challenges of hydraulic systems is crucial for effective and safe implementation across various industrial contexts. This research contributes significantly to the current understanding of the potential and challenges of using hydraulic systems to improve energy efficiency and operational performance in the industrial sector.Keywords— Hydraulic Systems, Energy Efficiency, Operational Performance